Light harvesting systems composed of carbazole based subphthalocyanine-BODIPY enhanced with intramolecular fluorescence resonance energy transfer (FRET). (January 2017) - Eçik, Esra Tanrıverdi; Özcan, Emrah; Kandemir, Hakan; Sengul, Ibrahim F.; Çoşut, Bünyemin
Abstract: A new series of subphthalocyanine-borondipyrromethene scaffolds containing N -ethylcarbazole moiety have been successfully designed and synthesized. The identities of synthesized compounds were confirmed by using 1 H, 13 C NMR, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The photophysical properties of the newly synthesized subphthalocyanine-borondipyrromethene conjugates were investigated via absorption and fluorescence spectroscopies in dichloromethane, tetrahydrofuran, benzene, and toluene solution (1 × 10 −5  M). The targeted compounds exhibit a highly efficient energy transfer process, either from the excited borondipyrromethene to the subphthalocyanine core or from the excited subphthalocyanine to the mono or distyryl borondipyrromethene unit. The time resolved fluorescence studies of the subphthalocyanine- borondipyrromethene conjugates were also examined. Graphical abstract: Highlights: Synthesis and characterization of new N -ethylcarbazole based Subphthalocyanine-BODIPY conjugates are represented. The photophysical properties of targeted compounds performed in benzene. The Energy transfer properties of the novel compounds have been investigated in benzene. The time resolved fluorescence studies of the carbazole based subphthalocyanine-BODIPY conjugates were examined.